Effect of the SISRUTE Online Referral System on Reducing Inappropriate Referrals at Advanced-Level Healthcare Facilities in Indonesia - Sulaiman Putra Nagaring; Agnes Ratna Saputri (Journal of Health Service Administration and Hospital Management, 2025)
This study addresses the widespread administrative inefficiency caused by inappropriate referrals within Indonesia’s tiered healthcare system, threatening the sustainability of the Jaminan Kesehatan Nasional (JKN) program. The purpose of this research was to quantitatively evaluate the impact of the Online Referral System (SISRUTE) implementation on reducing the inappropriate referral rate at Advanced-Level Healthcare Facilities (FKRTLs). Using a quantitative Segmented Time Series Regression Model (SRM), the analysis utilized national aggregated secondary data, defining the High Utilization Threshold (HUT) (75% adoption) as the intervention point. The results show a highly significant structural improvement post HUT, confirmed by a sustained decline in the inappropriate referral rate (β₃ = -1.15, p < 0.001), leading to a 55.2% overall decrease. Key administrative failures, such as incomplete data entry and mismatched service tiers, dropped by 79.4% and 72.2% respectively, validating SISRUTE’s role as a digital administrative gatekeeper. This evidence establishes SISRUTE’s effectiveness in optimizing resource allocation and enhancing patient flow, thereby directly supporting the financial sustainability of the JKN system. The study strongly recommends prioritizing and expanding mandatory digital referral systems like SISRUTE as a core strategy for robust national health governance and efficiency.